Outcome of monochorionic diamniotic twin pregnancies followed at a single center. (27th July 2015) - Fichera, Anna; Prefumo, Federico; Stagnati, Valentina; Marella, Daria; Valcamonico, Adriana; Frusca, Tiziana
Abstract: Objective: We aim to evaluate the outcome of a cohort of monochorionic diamniotic twin pregnancies followed from the first trimester onwards at a single center. Method: This was a retrospective analysis of prospectively collected data from a series of 300 monochorionic diamniotic twin pregnancies referred to our twin clinic between 2001 and 2012. Pregnancies were followed from the first trimester and fortnightly after 16 weeks of gestation. Data on pregnancy and neonatal outcome were analyzed. Results: There were two surviving infants in 259/300 (86.4%) pregnancies, one survivor in 22/300 (7.3%) and no survivors in 19/300 (6.3%) with an overall mortality of 60/600 (10%). Twin–twin transfusion syndrome was diagnosed in 33 cases (11%), isolated intertwin weight discordance ≥ 25% in 35 (11.6%) and major congenital structural anomalies in ten (3.3%). After 32 weeks, the prospective risk of spontaneous fetal intrauterine death was one in 248 (0.4%) per pregnancy. Conclusions: Despite specific prenatal fetal monitoring and management, monochorionic diamniotic twin pregnancies have still to be considered at high risk of mortality, although the prospective risk of intrauterine death after 32 weeks is low. Twin–twin transfusion syndrome and congenital anomalies were the main risk factors for mortality. © 2015 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Monochorionic diamniotic twin pregnancies are at high risk of mortality and morbidity. Series describing the outcome of monochorionic diamniotic twin pregnancies differ in study design, modality of pregnancy follow‐up and definition of complications. What does this study add? This series is representative of the outcome of monochorionic diamniotic twin pregnancies in contemporary clinical practice, based on a homogeneous cohort followed prospectively, at a single center, from the first trimester into the neonatal period.